Signal peptide peptidase-type proteases: versatile regulators with functions ranging from limited proteolysis to protein degradation - Lipp, Sara Suna; Lemberg, Marius (Journal of molecular biology, 2020)
Intramembrane proteases catalyze the unusual cleavage of peptide bonds in the plane of biological membranes. They are categorized according to their active site. The GxGD aspartyl proteases comprise presenilin, the signal peptide peptidase (SPP), and SPP-like (SPPL) proteases. Here we focus on the functionally related SPP and SPPL proteases, and review the current understanding of their substrate specificity and summarize known physiological functions in mammalian cells. We discuss how on the one hand regulated intramembrane proteolysis generates signaling molecules, and on the other hand how processes such as endoplasmic reticulum-associated degradation controls the quantity and activity of central regulators. While the enzymatic core of GxGD intramembrane proteases is conserved, association with regulatory factors and substrate adaptors may have tailored enzymes for various specific functions.
Gesehen am 24.09.2020